2017
DOI: 10.1080/10428194.2017.1375109
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Agent Orange exposure on prognosis and management in patients with chronic lymphocytic leukemia: a National Veteran Affairs Tumor Registry Study

Abstract: Exposure to Agent Orange (AO) has been associated with the development of chronic lymphocytic leukemia (CLL). We performed a retrospective study of 2052 Vietnam veterans identified in the National VA Tumor Registry to assess the impact of AO exposure on CLL prognosis, treatment and survival. Prognostic factors did not differ based on exposure. Veterans exposed to AO were diagnosed younger (63.2 vs. 70.5 years, p < .0001) and had longer overall survival (median not reached vs. 91 months, p < .001). This prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…46 The data suggest that Agent Orange exposure is associated with a younger age at CLL diagnosis but does not lead to poor prognosis or worsened overall survival. 47 Whether radiation exposure can promote CLL development is not fully understood. Initially the lack of CLL cases in Japan after the bombing of Hiroshima and Nagasaki, and the absence of CLL in short-term follow-up of people exposed to radiation for benign conditions, suggested that radiation does not cause CLL.…”
Section: Environmental Risksmentioning
confidence: 99%
“…46 The data suggest that Agent Orange exposure is associated with a younger age at CLL diagnosis but does not lead to poor prognosis or worsened overall survival. 47 Whether radiation exposure can promote CLL development is not fully understood. Initially the lack of CLL cases in Japan after the bombing of Hiroshima and Nagasaki, and the absence of CLL in short-term follow-up of people exposed to radiation for benign conditions, suggested that radiation does not cause CLL.…”
Section: Environmental Risksmentioning
confidence: 99%
“…Exposure to pesticides, specifically deltamethrin (Leon et al 2019), and herbicides (Alavanja et al 2014;Coggon et al 2015) has been associated with the development of CLL; the most convincing is Agent Orange used during the Vietnam War (Baumann Kreuziger et al 2014;Mescher et al 2018). Radon exposure has shown a similar relationship (Schwartz and Klug 2016).…”
Section: Environmental Considerationsmentioning
confidence: 99%
“…Studies have assessed the link between AO and MGUS as well as AO to various leukemias, such as chronic lymphocytic leukemia. 8,9 Other studies have shown the relationship between AO exposure and worse outcomes in persons with MM. 10 To date, only a single abstract from a US Department of Veterans Affairs (VA) medical center has investigated the relationships between AO exposure and MGUS, MM, and the rate of transformation.…”
Section: Introductionmentioning
confidence: 99%